Types and Linguistic Forms of Adjectives: A Comparative Semitic Study - Zaki, Farah; Mohamed , Laith (Al-Adab Journal, 2026)
The subject of the present study, "Types and Linguistic Forms of Adjectives -A Comparative Semitic Study-" constitutes a significant area of inquiry as it encompasses three Semitic languages: Syriac, Arabic, and Hebrew. This research aims to illuminate a critical topic concerning the role of adjectives and their syntactic occurrences within sentences. The primary focus of this investigation is to draw comparisons among the three languages (Syriac, Arabic, and Hebrew) regarding the adjective. This subject represents a linguistic phenomenon that is prevalent across all Semitic languages; however, distinctions and convergences undoubtedly arise due to the cultural variations inherent to each language under examination. It is noteworthy that this linguistic study adopts a comparative methodology to elucidate the similarities and differences among the three languages. Additionally, a descriptive approach is employed to provide an accurate delineation of adjectives within each of the study languages. The research addresses both the types and linguistic forms of adjectives, along with their degrees. Two primary categories of adjectives are identified: real and causal. Furthermore, six distinct forms are elaborated: comparative adjectives, superlatives, relative adjectives, state adjectives, active participles, and passive participles. The analysis also encompasses three degrees of adjectives: the degree of comparison, the degree of preference, and the degree of exaggeration.